Solomon Islands High Frequency Phone Survey on COVID-19 : Results from Round 1 - World Bank (World Bank, Washington, DC, 2020)
The Solomon Islands is a lower middle income small island state in the Melanesian region of the Southwest Pacific. Agriculture, including logging, is central to the economy of the Solomon Islands. To protect the country from importation of Coronavirus (COVID-19) and to limit the possible spread of undiagnosed cases, beginning March 27, the government enacted a series of emergency measures under the State of Public Emergency (SoPE). Coronavirus (COVID-19) response measures, both domestically and abroad, are expected to have negative impacts on the economy and on livelihoods. A strong evidence base is needed to understand the socioeconomic implications of the coronavirus pandemic for the Solomon Islands. The objective of this survey was to measure the socioeconomic impacts of the Coronavirus (COVID-19) global pandemic in the Solomon Islands, including livelihoods, food security, and public safety and security, through a high frequency mobile phone survey.